Techno-economic Analysis of Wind Turbines Powering Rural of Malaysia - Al-Fatlawi, Ali Wadi; Al-Baghdadi, Maher Ali; Togun, Hussein; Ahmadi, Goodarz; Rahman, Saidur; Rahim, Nasrudin Abd (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The purpose of this study is to evaluate the wind energy potential and energy cost of various types of wind turbines that could be powering rural Areas. The analysis was performed on hourly wind data over three years for five locations measured with a 10 m-high anemometer in Peninsular Malaysia. The performance of wind turbines with varying hub heights and rated power was examined. The economic evaluation of wind energy in all sites was based on an analysis of the annual Levelized cost of energy. Results show that the annual mean wind speeds vary from 1.16 m/s in Sitiswan to 2.9 m/s in Mersing, whereas annual power varies from 3.6 to 51.4 W/m2. Moreover, the results show that the cost of unit energy varies between (4.5-0.38) /kWh.The most viable site for the use of wind turbines was Mersing, while Sitiawan was the least viable site. A case study examined three wind turbine models operating at Mersing. The study showed that increasing the inflation escalation rate for operating and maintenance from 0-5% led to a decrease in the unit energy cost by about 38%. However, increasing the operating and maintenance escalation rate from 0-10% led to an increase in the unit cost of energy by about 7-8%.Â Â